2017
DOI: 10.1002/jbmr.3178
|View full text |Cite
|
Sign up to set email alerts
|

Teriparatide Treatment Improves Bone Defect Healing Via Anabolic Effects on New Bone Formation and Non-Anabolic Effects on Inhibition of Mast Cells in a Murine Cranial Window Model

Abstract: Investigations of teriparatide (rPTH) as a potential treatment for critical defects have demonstrated the predicted anabolic effects on bone formation, and significant non-anabolic effects on healing via undefined mechanisms. Specifically, studies in murine models of structural allograft healing demonstrated that rPTH treatment increased angiogenesis (vessels <30μm), and decreased arteriogenesis (>30 μm) and mast cell numbers, which lead to decreased fibrosis and accelerated healing. To better understand these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 71 publications
(169 reference statements)
4
21
0
Order By: Relevance
“…In 1967, Lindholm and colleagues described a progressive increase of MCs in the periosteal callus in a rat tibial‐fracture model . This was confirmed by other authors, who found an increased MC number in the early soft callus around blood vessels . Notably, MCs were also observed in the later bony callus near bone resorption sites.…”
Section: Introductionmentioning
confidence: 76%
“…In 1967, Lindholm and colleagues described a progressive increase of MCs in the periosteal callus in a rat tibial‐fracture model . This was confirmed by other authors, who found an increased MC number in the early soft callus around blood vessels . Notably, MCs were also observed in the later bony callus near bone resorption sites.…”
Section: Introductionmentioning
confidence: 76%
“…repair (Banovac, Renfree, Makowski, Latta, & Altman, 1995;Lindholm et al, 1969) have recently been substantiated (Behrends et al, 2014;Behrends et al, 2017;Ramirez-Garcia-Luna et al, 2017;Zhang et al, 2017). Taken together, these studies suggest that impaired recruitment of mast cells during bone repair leads to disruption of macrophage, vascular endothelial, and bone cell function, culminating in failure to heal.…”
mentioning
confidence: 85%
“…Resolution of this acute inflammatory reaction to tissue injury, mediated primarily by neutrophils and M1 macrophages, is arguably the most critical stage of wound healing (Claes, Recknagel, & Ignatius, ). Early reports suggesting that mast cells play a key role in the inflammatory phase of bone repair (Banovac, Renfree, Makowski, Latta, & Altman, ; Lindholm et al, ) have recently been substantiated (Behrends et al, ; Behrends et al, ; Ramirez‐Garcia‐Luna et al, ; Zhang et al, ). Taken together, these studies suggest that impaired recruitment of mast cells during bone repair leads to disruption of macrophage, vascular endothelial, and bone cell function, culminating in failure to heal.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of the vasculature within the BM is believed to play significant roles in bone biology . Recent IVI studies have visualized the dynamics of a series of characteristics of the vascular network such as the diameter , area , location , and permeability , as shown in Figure A . This is achieved by intravenous perfusion of fluorophore like dextran‐FITC, or more specifically, fluorescently labeled antibodies targeting vascular endothelium .…”
Section: Imaging Of Vesselsmentioning
confidence: 99%
“…However, while angiogenesis (vessels<30 μm) is beneficial to bone healing, arteriogenesis (vessels>30 μm) conduces to fibrotic scaring, indicating a diameter‐dependent effect. Accordingly, Zhang et al underlined the non‐anabolic effect of recombinant parathyroid hormone in bone healing through mast cell inhibition, since mast cells impede bone healing by stimulating arteriogenesis.…”
Section: Imaging Of Vesselsmentioning
confidence: 99%